EKONOMI POLITIK BANTUAN KEUANGAN PEMERINTAH DAERAH DI DESA TASIK JUANG KECAMATAN LUBUK BATU JAYA KABUPATEN INDRAGIRI HULU TAHUN 2011 – 2015 - Trania, Sella Versi; M, Erman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The purpose of this study analyzes the political economy aspects of the implementation of the financial assistance of local government at Desa Tasik Juang Jaya subdistrict of Lubuk Batu Indragiri Hulu in 2011 - 2015. The village is the basis of economic and political power that needs serious attention from the government. This makes the development planning for rural development as the object and not as a subject of development again. Political arena of local budgets is happening now continuously shown local government. At least through the third paragraph of Article 212 of Law 32/2004 (substitutes Law No. 22/1999), local governments are given wide space to perform budgetary policy to the village. The discretion of local governments (counties) in the budgeting to the villages, stagnated against Law No. 22/1999. Despite the progress editorial in describing the source of village income (note Article 212 paragraph 3 point c of Law No. 32/2004), still create an impression of the village's financial fate handed to local governments / districts. Construction of thought believes that the village has not been able to be independent, have limited human resources, and weak financial management. Results showed a significant difference between the required amount of funds available on the RKP village in the Medium Term Development Plan Rural (RPJMDes) prepared by the Village Government and the elements of society with a number of Budget Village (APBDes) each year is indications of problems in financial planning and management in Desa Tasik Juang. The condition indicates the intervention of local government in the planning and preparation of particular postal APBDes Financial Assistance Provincial / District / City. The politicization of the budget has already occurred in the village of Tasik Juang. One eye revenue budget very strategic financial help local governments to target politicization, apparently showing an impressive amount of decline in 2015. Even the likelihood that the role of community participation through Musrenbang just sham and a pretense (Camouflage). This led to the development programs implemented by government Desa Tasik Juang do not correspond to the Village Government Work Plan (RKPDes).Kata kunci : Budget Political Economy, Rural and Regional Government Financial Assistance